Agraphia in Bulbar-Onset Amyotrophic Lateral Sclerosis: Not Merely a Consequence of Dementia or Aphasia - Hiroo Ichikawa; Nobuyoshi Takahashi; Soutaro Hieda; Hideki Ohno; Mitsuru Kawamura (Behavioural Neurology)
The clinical significance and characteristics of writing errors in bulbar-onset amyotrophic lateral sclerosis (ALS) are not clear. We retrospectively investigated writing samples in 19 patients with bulbar-onset ALS without preceding extra-motor symptoms. Co-development of dementia and/or aphasia was also explored and single photon emission computed tomography (SPECT) images of the brain were reviewed. As a result, a high prevalence of writing errors (15 of the 19 patients) was found. Of note were isolated writing errors with neither dementia nor aphasia verified in 2 patients whose dysarthria was mild enough to evaluate spoken language. The remaining 13 patients also showed agraphia, but either dysarthria was too severe to evaluate aphasia or frontotemporal dementia (FTD)-like features co-existed. Of these patients, one who initially lacked dementia subsequently developed FTD-like features. The frequent writing errors were omission or substitution of kana letters and syntactic errors. SPECT images showed bilateral or left-side dominant hypoperfusion in the frontotemporal lobes as a consistent feature. These results show that patients with bulbar-onset ALS frequently exhibit agraphic writing errors and that these are not merely consequences of dementia or aphasia. However, these writing errors may indicate the involvement of frontotemporal language-related areas beyond the primary motor cortex.